Blood borne diseases. Risk and prevention of the surgical team. - Odriozola, Martín; Paganini, Juan José; Lima, Edgar (Cirugía del Uruguay, 2003)
The authors attempt to update a tapie which is currently highly sensitive and covers medical, le-gal, ethical, epidemiological and technical aspects. It comprises and adequate valuation of actual infection risk due to labor accidents so as to establish behavior pattems when such accidents do occur. The paper in eludes a series of biosecurity criteria recommendations targeted at reducing the number of such accidents and their consequences.